Knowledge, Attitude and Awareness of Adolescence Hypertension among Student Nurses in a Tertiary Institution in Kwara State - Ibrahim Opeyemi; Ahmad Ridwanullah; Eze Muhammed Suleiman; Ibraheem Mulikat Ayoade; Kazeem Ayinla; Imam Abubakar Ayinla; Abubakar Maryam Kehinde; Imam Rasheedah Toluwase; Ibrahim Ahmed Orelope; Abiodun Lawal Sebioniga (Archives of Case Reports, 2025)
Background: Adolescent hypertension is an emerging public health concern with serious long-term cardiovascular risks if left untreated. Early identifi cation, awareness, and preventive measures are essential in managing this condition, particularly among healthcare providers who play a critical role in health promotion and patient education. Aim: This study aims to assess the knowledge, attitude, and awareness of adolescent hypertension among student nurses at Kwara State College of Nursing, Oke-Ode, Kwara State. The research seeks to identify the students’ understanding of adolescent hypertension, their attitude towards its prevention, and their awareness of its long-term health consequences. Methodology: A descriptive cross-sectional design was employed, utilizing a structured questionnaire distributed to 255 students which 230 responses were retrieved from the respondents. The questionnaire assessed demographic information, knowledge of adolescent hypertension, attitudes towards its prevention, and awareness of its risks. Data were analyzed using descriptive and inferential statistics to determine the level of knowledge, attitudes, and awareness. Results: The fi ndings revealed that while a signifi cant proportion of students demonstrated moderate knowledge of adolescent hypertension, critical gaps were observed in their understanding of specifi c risk factors, complications, and management strategies. Although most participants exhibited positive attitudes towards adopting healthy lifestyles to prevent hypertension, only a minority actively practiced regular physical activity or followed a healthy diet. Awareness of the importance of regular blood pressure monitoring was high, yet inconsistent in practice among the students. Conclusion: The study concludes that although student nurses have a basic understanding of adolescent hypertension, there is a need to improve their knowledge and practical engagement in preventive measures. Efforts to strengthen nursing education through enhanced curriculum content, practical training, and health promotion activities are recommended to better prepare student nurses for addressing adolescent hypertension in clinical settings.